Biophilia Meets Literature: Designing Social Spaces for Reading and Interaction - Dipali Mukherjee; Deepti Pande Rana; Swetika Porwal (Emerging Trends in Languages, 2024)
This research explores the intersection of biophilic design principles and literary spaces, focusing on creating social environments that promote reading and interaction. It has been demonstrated that biophilic design, which incorporates natural elements into constructed settings, improves productivity, well-being, and creativity. By incorporating these principles into libraries, bookstores, and reading nooks, we aim to foster spaces that not only encourage literary engagement but also support social connectivity. This paper examines various case studies of biophilic design in literary settings, analysing their impact on user experience and community building. Through surveys, interviews, and observational studies, we assess how natural light, indoor plants, water features, and natural materials influence readers' satisfaction and social interaction. The findings suggest that biophilic literary spaces can significantly enhance the enjoyment of reading and promote a sense of community. This research contributes to the growing field of biophilic design by highlighting its potential to transform literary environments into vibrant, interactive social hubs. In a world where digital communication frequently supplants in-person contacts, biophilic reading spaces can foster social settings that promote conversation, experience sharing, and cross-cultural engagement. By integrating natural materials, patterns, and forms into the architectural and interior design of libraries, bookstores, and other literary spaces, designers can create environments that are not only aesthetically pleasing but also restorative and conducive to learning.
Keywords: Biophilic Design; Natural light; indoor plants; literary spaces; sustainable materials